The red maze - Siegel, Mark, 1967-; Siegel, Alexis (Siegel, Mark, 1967- 5 worlds, 2019)
"Oona, Jax Amboy, and An Tzu must light the beacon on Moon Yatta and stop the evil force that threatens to rule the 5 worlds"--